Effects of Medicinal Plant Extracts as Pre-milking Teat Dip to Reduce Teat-end Bacterial Load in Lactating Dairy Cow - Todtong, Pranpreya (Journal of Mahanakorn Veterinary Medicine, 2023)
The aim of this experiment was study the effects of medicinal plant extracts as pre-milking teat dip to reduce teat-end bacterial load in lactating dairy cow. The experimental design was a Completely Randomized Design (CRD) of 6 treatments follow as types of medicinal plant extracts such as Curcuma longa L., Nymphaea lotus L. (flower pollen), Nymphaea lotus L. (flower petals), Garcinia mangostana L., Durio zibethinus L. and Psidium guajava. L. The medicinal plant extraction by maceration method using 70 % methanol and drying by Freeze Dryer. Antibacterial activity testing of medicinal plant extracts by MIC and MBC. The efficacy testing of pre-milking teat dip solution in lactating dairy cows by comparing the total bacterial count on teat end before and after dipping the solution. The results of the study found that flower pollen of Nymphaea lotus L. (38.40 %) was highest % yield. The results of antibacterial activity testing found that Psidium guajava. L. extract was the most effective in inhibiting bacteria. The MIC and MBC values were against S. aureus (0.25 and 1 mg/ml) and E. coli (0.5 and 2 mg/ml). And the results of the efficacy of pre-milking teat dip solution found that the extraction of Curcuma longa L., Nymphaea lotus L. (flower pollen), Nymphaea lotus L. (flower petals), Durio zibethinus L. and Psidium guajava. L. was a statistically significant difference in reducing the total bacterial count of teat end (P<0.05). In conclusion, extracts from Curcuma longa L., Nymphaea lotus L. (flower pollen), Nymphaea lotus L. (flower petals), Durio zibethinus L. and Psidium guajava. L. can be applied as a pre-milking teat dip to reduce the teat end bacterial load in lactating dairy cows.